Photoelectrical properties of integrated photodetectors based on bilayer graphene quantum dots with asymmetric metal contacts: a NEGF-DFT study. Issue 3 (23rd December 2021) - Ghandchi, Majid; Darvish, Ghafar; Moravvej-Farshi, Mohammad Kazem
Abstract : We have developed the right atomic-molecular ab initio calculations-based model to investigate photoelectrical properties of photodetectors based on graphene nanodot structures with two probes. Abstract : We propose investigating the electro-optical properties of photodetectors based on mono- and bilayer graphene quantum dots or nanodots (GNDs). These photodetectors consist of dissimilar metals (gold, silver and titanium) that are in contact with the GNDs. To obtain photoelectrical characteristics, we employed density functional theory to solve the non-equilibrium Green's function. Photo-responsivities and quantum efficiencies obtained for these nanostructures were far better than those for structures based on graphene nanoribbons. Among the proposed photodetectors, the best performance belonged to the bilayer structures illuminated by in-plane polarized incident light. The proposed photodetectors operate without a need for externally applied voltage and are suitable for parallel light propagation using directional couplers based on the evanescent field of incident light; hence, they have applications in optical integrated circuits.